ANALISIS IMPLEMENTASI AUGMENTED REALITY (AR) PENGENALAN CANDI BERBASIS MOBILE ANDROID DI SD NU BAHRUL ULUM KOTA MALANG - Agustina, Rini; Barkah, Muhammad Avief (DINAMIKA DOTCOM, 2017)
Malang is one of the tourist areas in Indonesia which has many tourist attractions, among them theform of the temple. Temple merupaka history that can not be eliminated from our country, thecurrent tour of the temple in the city of Malang are rarely known or even visited by the public. Thisis particularly worrying given duty as good citizens, especially the younger generation successorto the nation is to maintain and preserve the cultural heritage of their ancestors.Distance and timeto make travel this temple is less attractive to the younger generation especially school students,and therefore designed an application that implements Augmented Reality to support interactivelearning introduction of the temples in Malang based on Android, which is expected to helpprovide motivation for generations young to begin to participate in maintaining and preserving thecultural heritage of his people.Key words: Malang Temples, Augmented Reality, Interactive Learning Media, Android.